The effects of reduced gill surface area on gas transfer in the rainbow trout (Oncorhynchus mykiss). - Julio, Alejandra E. (University of Ottawa (Canada), 2000)
The total functional surface area of the gills is a key component in gas exchange and any reduction would predictably limit both oxygen uptake and carbon dioxide excretion. But one might also hypothesise that under these conditions the fish might compensate. A reduction of 15, 30 and 40% of total anatomical gill surface area in rainbow trout was accomplished by the ligation of 1, 2 and 3 gill arches, respectively. With the use of an extracorporeal shunt, arterial blood gases were continuously monitored during normoxia and graded hypoxia. As well, a dorsal aortic cannula allowed for periodic blood sampling for such variables as total arterial oxygen content (CaO2), total arterial carbon dioxide content (CaCO2), haemoglobin concentration, haematocrit and circulating catecholamines. Oxygen uptake (M˙O2), carbon dioxide excretion rates (M˙CO2) and ventilation convection requirements for both gases were determined through measurements of inspired and expired water carbon dioxide content (CCO2) and partial pressure of O2 (PO2) differences as well as in-flowing/out-flowing water CCO2, and PO2 differences. A final series of experiments examined the effects of carbonic anhydrase injections in ligated versus sham-ligated fish as well as comparing these results to ligated fish injected with physiological saline. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.